Cannabidiol as a treatment for patients who are clinically at high risk of developing psychosis: learnings from the CANTOP-RCT - Sagnik Bhattacharyya; Cathy Davies; Ben Carter; Philip McGuire; Michael Brammer; Paolo Fusar-Poli; Matthew Broome; Stuart Watson; Jesus Perez; Alison Yung (Efficacy and Mechanism Evaluation)
Background There are no licensed pharmacological treatments for people who are at clinical high risk of developing psychosis. Although psychological interventions are well tolerated, they do not appear to reduce the risk of later transition to psychosis. Clinically high-risk people commonly experience low-grade anxiety and psychotic symptoms. Cannabidiol is a non-intoxicating substance present in cannabis that shows promise in terms of its antipsychotic and antianxiety potential. However, no fully powered randomised clinical trial has investigated the efficacy of cannabidiol as a treatment in people with clinical high risk. Further, the mechanisms that may underlie its beneficial effects remain unclear. Objectives To conduct a double-blind, placebo-controlled randomised controlled trial to investigate the efficacy of cannabidiol as a treatment for psychotic and anxiety symptoms in people at clinical high risk, its safety and tolerability, and the neurochemical and neurophysiological basis of its effects. Design We proposed to conduct a parallel-arm, multisite, double-blind randomised control trial to evaluate the efficacy and tolerability of cannabidiol when added to treatment as usual, compared to treatment as usual plus placebo, in 300 clinically high-risk patients (n = 150 per treatment arm). In a subsample of participants (total N = 100; n = 50 per treatment arm), we proposed to use magnetic resonance spectroscopy to measure hippocampal glutamate levels, functional magnetic resonance imaging to measure brain activation (while patients performed verbal memory and emotional processing tasks), and arterial spin labelling to measure blood flow to investigate the neurochemical and neurophysiological basis of the effects of cannabidiol (mechanism substudy). Setting Multicentre study involving early intervention services within the United Kingdom. Participants Three hundred patients aged 18–35 years (N = 300; n = 150 per treatment arm) diagnosed with a clinical high-risk state for psychosis and attenuated psychotic symptoms for the randomised controlled trial. A subsample of participants (total N = 100; n = 50 per treatment arm) for the mechanism substudy. Intervention Participants were to receive a single daily dose of 600 mg cannabidiol or placebo to be taken orally for 6 months. Main outcome measure Severity of psychotic symptoms at 6 months using the Comprehensive Assessment of At-Risk Mental States. In the mechanism substudy, we aimed to compare their effects following 28 days treatment on hippocampal glutamate levels, and on brain activation while performing verbal memory and emotional processing tasks, as well as resting regional cerebral blood flow in the medial temporal cortex and basal ganglia. Results Funding for the research commenced in September 2018, when we entered a planned 6-month study set-up phase. The trial was not able to be delivered in a timely manner due to uncertainty over the drug supply, leading to eventual closure of the study in March 2022. Conclusions Here we summarise the events that led to this decision, reflect on the contributing factors and suggest potential learning points to help other researchers avoid such outcomes in future. Study limitations and future work The CANTOP-RCT did not start owing to challenges in securing supply of the study drug, and therefore addressing this issue is essential for any future definitive study to investigate the efficacy of cannabidiol as a treatment for clinical high-risk patients with attenuated psychotic symptoms. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Efficacy and Mechanism Evaluation (EME) programme as award number 16/126/53. Plain language summary Psychosis is often preceded by a clinical high-risk state, when people have similar but shorter-lasting and less severe experiences than people with fully developed psychosis. As fully developed psychosis causes a great deal of suffering to patients and their families, there is growing interest in treating people at the clinical high-risk stage. However, current treatments for people in the clinical high-risk state do not work very well and are also not tolerated very well. Hence, at the moment, most people in a clinical high-risk state presenting to the National Health Service typically receive practical help and support from clinicians to address current issues. Cannabidiol, a naturally available chemical found in extracts of the cannabis plant, seems to be a promising candidate. However, we do not know whether cannabidiol treatment will actually be useful in relieving symptoms in clinical high-risk state patients. We received funding to test this in a large clinical trial comparing cannabidiol to placebo (a sugar pill with no active ingredient). We aimed to study 300 clinical high-risk state patients. Half of them were supposed to receive the same dose of cannabidiol (600 mg/day) that we have used before and the other half were supposed to receive a matching dummy capsule. Neither the researchers nor the patients were supposed to know what each person received during the study. At the end of 6-month treatment, we wanted to examine whether those who received cannabidiol were significantly better compared to those who received the sugar pill. We also aimed to use brain scanning in a subgroup of people (50 from each treatment group) to understand how cannabidiol might work. However, despite our best efforts, it was challenging to find a supply of high-quality cannabidiol for the trial. The COVID pandemic also posed challenges. As a result, the study was closed down before the trial could even start.